Drivers of use and adoption of bundled climate-smart agriculture and climate information services in Northern Ghana - Mahama, O.K.; Abukari, A.T.; Damba, O.T.; Mponela, P.; Dalaa, M.A.; Yeboah, S.; Adomaa, F.O.; Tepa-Yotto, G.; Segnon, A.C.; Zougmore, R.; Tamo, M. (2025)
Purpose The purpose of this study is to assess the extent of use and adoption of bundled climate-smart agriculture (CSA) and climate information service (CIS) in Northern Ghana. Design/methodology/approach This paper analyzed farmers’ preferences for bundled CSA–climate information (CI) practices that not only promote climate resilience but also address health, gender and social inclusion as drivers of adoption. Using a multivariate probit and multinomial probit method, findings revealed that prioritization based on improved health, gender sensitivity and social inclusivity influences the adoption of CIS, leguminous crop rotation, organic improvement of soil, pest/disease tolerance varieties and stress-tolerance varieties in Ghana. More than one of these technologies is bundled with CI to address water stress and maintain soil moisture while improving crop yields. Adoption and prioritization of technologies were based on age, as older farmers were inclined to pest- and disease-tolerant varieties combined with CI compared to the female farmers. The multivariate probit model is used to assess the differential adoption of CSA technologies in the study area. Findings Access to CI, leguminous crop as a previous crop to a main crop, organic soil amendment, pest- and disease-tolerant varieties and drought- and stress-tolerant varieties are highly adopted and prioritized by the farmers in Northern Ghana. The findings of this study also revealed a differential adoption of CSA technologies, and this difference is driven by the age of a farmer, as labor-intensive technologies are less adopted by older farmers. Research limitations/implications Pest- and disease-tolerant varieties combined with CI require fewer labor days with less cost compared to other pest and disease control measures. This is critical, as the gap in CSA–CIS knowledge emanates from a lack of awareness of the appropriate usage of these technologies. Bundled CSA–CIS technologies in Northern Ghana require appropriate location-specific and age-differential-driven products developed around sustainable financing scheme with private sector involvement. Practical implications There is a need to identify less labor-driven CSA-CI technologies and services to address both age and gender roles. This will enhance the use and adoption of bundled CSA-CI technologies. Social implications This study addresses the needs of gender and age differential in technology use and adoption among smallholder farmers in Northern Ghana. Originality/value This study is original and has not been conducted elsewhere.